A comprehensive review on heat and mass transfer simulation and measurement module during the baking process - Sourav Chakraborty; Kshirod Kumar Dash (Applied Food Research, 2023)
The application of computational fluid dynamics (CFD) for controlling quality boundaries in light of temperature and moisture profiling is detailed in this review. For the mapping of intricate stream design inside the baking oven and its product-based baking interaction, efficient utilization of CFD perspectives can be observed. The most crucial element in baking that affects product quality is temperature. Based on heat transfer, the CFD model proved effective in estimating the product's crumb and crust temperatures. In addition to time and temperature, the position of the dough inside the oven affects the quality of the finished product during baking. CFD demonstrating angles effectively predicts the temperature profiles inside the baked product and henceforth, assists with controlling the extreme quality of the product. Regardless, also demonstrating studies ought to be embraced including mass transport and volume extension during the baking process. A piece of the issues related to moisture and heating measures during exhibiting of bread, bun, and cookies baking process, have been included. This study exhibits CFD to be a significant tool for the simulation of the baking oven and relative expectation of temperature and moisture profiles which eventually impacts starch gelatinization and browning issue during the baking process. The mass transfer during baking and volume expansion of various bakery products can also be modelled using CFD.